Pengaruh Gender, Umur, Tekanan Ketaatan, Kompleksitas Tugas, Dan Pengalaman Auditor Terhadap Audit Judgement(Studi Empiris Pada KAP di Kota Surakarta dan Yogyakarta) - Yanuar, Randy; , Dra. Rina Trisnawati, Ak, SE, MM (2016)
This study aimed to analyze and prove the influence of gender, age, pressure obedience, complexity of the task, as well as the experience of auditors on the audit judgment in the case study on KAP in Surakarta and Yogyakarta. This research is a quantitative survey method in the form of an explanatory research and hypothesis testing. The research sample is the auditor who worked on Public Accounting Firm (KAP) in Surakarta and Yogyakarta is willing to be the object of research. The sampling technique used is convenience sampling. Data obtained by distributing questionnaires to auditors working in KAP Surakarta and Yogyakarta and analyzed using multiple regression analysis through SPSS version 17.0. These results indicate that age, obedience pressure, the complexity of the task and the auditor's experience influence on audit judgment, while gender has no effect on audit judgment on KAP in Surakarta and Yogyakarta.